Spontaneous bladder perforation unrelated to trauma or surgery. (12th June 2014) - Cusano, Antonio; Abarzua-Cabezas, Fernando; Meraney, Anoop
Abstract : Urinary bladder ruptures (UBR) typically result from either blunt or penetrating trauma, or from iatrogenic surgical injuries. Patients typically present with symptoms including lower abdominal pain, haematuria, dysuria and anuria. Here, we report on a rare case of spontaneous bladder perforation. A 60-year-old, Caucasian woman initially presented with lower abdominal pain and diarrhoea, and was subsequently found to have an elevated serum creatinine level. A CT cystogram revealed a leak from the bladder. The patient consented to exploratory laparotomy and repair of the non-traumatic bladder perforation. At the time of the last follow-up, given the fact that the patient's urodynamics were unremarkable and that she was emptying her bladder well (repeat postvoid residual was zero), the patient was informed that she did not require future urological follow-up unless difficulties arise.